The effect of autogenous tooth bone graft material without organic matter and type I collagen treatment on bone regeneration - Min-Gu Kim; Jung-Han Lee; Gyoo-Cheon Kim; Dae-Seok Hwang; Chul-Hun Kim; Bok-Joo Kim; Jung-Han Kim; Uk-Kyu Kim (SpringerOpen, 2021)
Abstract Objectives The aim of this study is to examine the effect of particulate autogenous tooth graft removed with organic matter and type I collagen addition on bone regeneration and to validate the possibility of useful allograft material for jaw defects. Material and methods Autogenous tooth bone maker (Korean Dental Solution® KOREA) made particulate autogenous tooth not including organic matter. We used to the developed tooth grafts for experiment. Cell adhesion test with hemacytometer and energy dispersive X-ray spectroscopy (Supra40 VP®, Carl Zeiss, Germany) analysis about the particulate autogenous tooth and type I collagen were performed. Rabbits were divided into three groups: bone graft with organic matter (OM) removing particulate autogenous tooth group, bone graft with OM removing particulate autogenous tooth and type I collagen group, and a control group. Bone grafting was performed in rabbit's calvaria. The rabbits were sacrificed at different interval at 1, 2, 4, and 6 weeks after bone grafting for the histopathologic observation and observed the effect of bone regeneration by SEM, H-E & Masson stains, osteocalcin IHC staining. Result In vitro cytopathological study showed affinity for cells, cell attachment pattern, and cell proliferation in the order of control group, OM-removed and collagen-treated group, OM-removed particulate autogenous tooth group. The results of the degree of mineralization were opposite to those of the previous cell experimental results, and the OM-removed group, OM-removed group and collagen-treated group were relatively higher than the control group. Histopathologic analysis showed that vascularization and neonatal bone formation were higher in particulate autogenous tooth group with removing OM and with addition of collagen than control group and group of OM removed only. Immunohistochemical analysis showed that osteocalcin (OSC) expression was not observed in the control group, but at 4 weeks groups, OSC expression was observed the OM removed and OM-removed-collagen-treated particulate autogenous tooth, and the degree of expression was somewhat stronger in group of the OM removed and collagen additionally treated particulate autogenous tooth. Conclusion Particles that do not contain organic matter, the saint tooth, was responsible for sufficient bone graft material through the role of space maintenance and bone conduction, and further improved bone formation ability through additional collagen treatment. Therefore, research on various extracellular substrates and autologous bone grafting materials is necessary, and through this, it is possible to lay the foundation for a new type of autologous bone grafting material with excellent academic and technical utility.